Pathomorphological and Immunohıstochemical Evaluation of Unilateral Progressive Mooren’s Ulcer in a Cat - Alcigir, Mehmet Eray; Kutlu, Tuncer; Ergin, Irem; Karabulut, Sefika; Alcigir, Gunay (Acta Scientiae Veterinariae, 2018)
Background: Mooren’s ulcer is a chronic and painful ulceration of the cornea. It begins progressively in the periphery and spread centrally in cornea. In human, it is seen uniaterally in most of cases. Mooren ulcer has not been reported in any kind of animals up to now. Although its aetiology is not completely enlighted, it has been suspected of the inflammatory reaction against injuries-microbiological and immun mediated effects. Immun response in presence of accumulation of immune complexes into the limbal vessels.As a result of the deficit in the regulatory mechanism because the number of suppressor cells control over B and T lymphocytes, These situations can result in a progressive tendancy to inflammation because the production of autoantibodies and/or lymphokine from cytotoxic T-lymhocytes creates an immune-mediated vasculitis. Numerous immigrant inflammatory cells and proteins are evaded from vessels. After triggering inflammatory cells and releasing of meditors, corneal vascularization, scar tissue and re-epithelization develop. This regenerative-reperative process plays an important role during post-inflammatory process. Case: In this case, it was aimed to detect pathomorphological structure and immunologic relations in progressive Mooren’s ulcer (MU). A 1 year-old mix breed cat was submitted to clinic with complaints of progressive painful and eyesight loss in left eye. There were 1 cm-ulceration, opacification and old haemorrhagic areas at peripheral cornea. Histopathologically, there was wide ulceration including all layers of corneal epithelium and particularly vacuolar degeneration at suprabasal cells. In corneal stroma, numerous neutrophiles and mononuclear cells were infiltrated. Neovascularisation and fibrosis beginning from limbus were also present. This fibrotic progress was confirmed by Masson’s trichrome staining method. Immunohistochemically, Cytokeratin 3 (CK3) and cytokeratin 12 (CK12) positivities showing regenerative activity of suprabasal and basal cells were not widespread. Epidermal Growth Factor (EGF) positivities were generally weak in epithelial cells. In stroma, moderate vimentin positivities were detected proliferated in fibrocytes originating from limbus. α1-antichymotrypsin (A1AC) was mildly reacted in neutrophiles. CD3 and CD4 confirmed the presence of regulatory and helper T lymphocytes. CD3 and CD8 marked cytotoxic T lymphocytes and CD20 marked B lymphocytes in inflammatory areas. CD34 were also positive in peripheral corneal stem cells derived from limbal basal epitheliums in partly regenerated area. CD57 positivity in T lymphocytes and NK cells and CD68 positivity in macrophages were attended to the area. Discussion: CD1a positivity in T lymphocytes proved mediating lipid and microbial origin glycolipid antigens. TUNEL reactions showing DNA in situ fragmentation were present in the destructive and aging epithelial cells at periphery. In conclusion, the case has been found as unique in terms of its immunohistochemical characterization. The markers show that CD1a and CD68 expressions follow different progress in animals unlike in humanbeings even though the ulcer of pathogenetic mechanism is found identical to humanbeings.. The roles of CD20 and CD57 markers have potential roles in this ulcer. It is also concluded that insufficient epithelial regeneration, fibrosis, inflammation and apoptosis showed progressive Mooren’s ulcers having possibly microbial origin. Keywords: Mooren’s ulcer, pathomorphology, immunohistochemistry, cat.